Penentuan Interval Waktu Penggantian Komponen Kritis Pada Mesin Volpack Menggunakan Metode Age Replacement - Yanuar Yuda Prawiro (Jurnal Teknik Industri, 2015)
CV. Cool Clean is a company engaged in packing tissue. During this time the company only perform corrective action that causes disruption of the production process due to frequent damage of a sudden the engine components volpack. In this study used a model of preventive replacement that can reduce downtime and costs. The method used to obtain the schedule interval a critical component is age replacement method. Seal heater obtained replacement time interval of 30 days with a 22% reduction in downtime. Replacement interval for knife foil is 26 days with a 27% reduction in downtime. Replacement interval for solenoid valve is30 days with a 29% reduction in downtime. Replacement interval forOring seal is 18 days with a 29% reduction in downtime. Replacement interval for needle bearing is 62 days with a 25% reduction in downtime. Results of this study also showed that by applying age replacement can save costs for seal heater Rp. 974.000 or 23%. Knife foil cost savings of Rp. 1.251.409 or 22%. Solenoid valve cost savings of Rp.546.539 or 24%. Oring seal cost savings of Rp. 350.096 or 26%. And needle bearing cost savings of Rp. 196.712 or 26%.